Pertumbuhan dan Mortalitas Ikan Endemik Opudi (Telmatherina prognatha Kottelat, 1991) di Danau Matano, Sulawesi Selatan - Andi Chadijah; Sulistiono Sulistiono (Jurnal Ilmu Pertanian Indonesia, 2021)
Lake Matano is an ancient lake that has a high endemicity. Opudi fish (Telmatherina prognatha) is an endemic fish that is vulnerable to extinction and needs to be preserved. The threat of invasive species and habitat degradation can cause a decrease in opudi fish populations. This study aimed to examine the growth parameters associated with growth coefficients and mortality in Lake Matano so that population can be sustainable. The study was conducted at Lake Matano from March 2018 to February 2019. Samples of fish were caught using a net bag measuring 30 m long, 2 m wide with a mesh size of 0.5 inches. Analysis of fish growth was based on total length-frequency data. These data were analyzed using the FISAT II software. The sizes of male and female opudi fish obtained ranged from 30-70 mm. Growth patterns of von Bertalanffy butina in male fish are male Lt = 76.50 [1-e-0.46 (t + 0.47)] and female fish Lt = 74.05 [1-e-0.51 (t + 0.52)]. The total mortality value of male fish was higher (Z = 1.65) compared to female fish (Z = 1.50), the natural mortality value of male opudi fish was lower (M = 0.84) compared to that of female fish (M = 0.91). Keywords: endemic fish, growth, mortality, Telmatherina prognatha